Photoinduced electron transfer in host-guest interactions of a viologen derivative with a didansyl-pillar[5]arene. (June 2022) - Pisagatti, I.; Crisafulli, D.; Pappalardo, A.; Trusso Sfrazzetto, G.; Notti, A.; Nastasi, F.; Parisi, M.F.; Micali, N.; Gattuso, G.; Villari, V.
Abstract: With the goal of understanding the electron transfer mechanism of fluorophore-functionalized pillararenes, a pillar[5]arene bearing two dansyl fluorophore moieties at the opposite rims of its cavity has been synthesized, and the behavior of such a new host molecule has been thoroughly investigated in the presence of an N, N′ -di-(6-bromohexyl)-viologen derivative. 1 H NMR, NOESY and DOSY experiments demonstrated that the pillar[5]arene recognizes the viologen derivative, forming a 1:1 host-guest complex by including one of the two bromoalkyl chains within its π-rich cavity. Photophysical and electrochemical studies revealed that, upon guest addition to the host, the fluorescence intensity of the complex is progressively quenched by a photoinduced electron transfer process (PET) from one of the dansyl groups of the host to the viologen moiety of the guest. Graphical abstract: Image 1 Highlights: A pillar[5]arene bearing two dansyl fluorophore moieties has been synthesized. The pillararene forms a 1:1 complex with N, N′ -di (6-bromohexyl)-bipyridinium. Fluorescence of the complex is progressively quenched by a dansyl-to-viologen PET.